Equality-Efficiency Trade-off within French and German Couples - A Comparative Experimental Study - Miriam Beblo; Denis Beninger; Francois Cochard; Helene Couprie; Astrid Hopfensitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We present the results of an experiment that measures social preferences within couples in a context where intra-household pay-off inequality can be reduced at the cost of diminishing household income. We measure social norms regarding this efficiency-equality trade-off and implement a cross-country comparison between France and Germany. In particular, we show that German households are more inequality averse and are thus less efficient than French households. A decomposition of this difference reveals that approximately 40% is driven by diverging sample compositions in the two countries, while 60% of the initial French/German difference remains unexplained. Beliefs differ significantly from observed behavior in both countries. Efficient choices are overestimated in the German sample and underestimated in the French.
Keywords: D13; C91; C92; 330